Understanding the Real State of Human Adult Hippocampal Neurogenesis From Studies of Rodents and Non-human Primates - Seki, Tatsunori (Frontiers in Neuroscience, 2020)
The concept of adult hippocampal neurogenesis (AHN) has been widely accepted, and a large number of studies have been performed in rodents using modern experimental techniques, which have clarified the nature and developmental processes of adult neural stem/progenitor cells, the functions of AHN, such as memory and learning, and its association with neural diseases. However, a fundamental problem is that it remains unclear as to what extent AHN actually occurs in humans. The answer to this is indispensable when physiological and pathological functions of human AHN are deduced from studies of rodent AHN, but there are controversial data on the extent of human AHN. In this review, studies on AHN performed in rodents and humans will be briefly reviewed, followed by a discussion of the studies in nonhuman primates. Then, how data of rodent and nonhuman primate AHN should be applied for understanding human AHN will be discussed.